Classification of road sections according to the degree of danger to the formation of a wear track - A. S. Aleksandrov; T. V. Semenova; D. Yu. Raskoshny (Вестник СибАДИ)
Introduction. The intensification of the motorization of the Russian population has led to a significant increase in the number of passenger cars, which in many regions are supplied with studded tires for the winter period. This circumstance led to the large-scale appearance of a certain type of ruts caused by the wear of asphalt concrete pavement from the action of studded tires and abrasive materials used to combat winter slipperiness. The track formed on the surface of road surfaces has a complex character and includes three types of tracks: structural, shear track and wear track. The contribution of each type of track to the total depth of the complex track is different and depends on the characteristics of transport loads, the properties of the coating material, and weather and climatic factors.Materials and methods. The wear track is formed in winter from the impact of studded tires, and its depth is affected by many factors: the mode and intensity of movement of cars with studded tires, the type of spikes, their number on the tire, the size of the protrusion of the working insert of the spike, the properties of asphalt concrete pavement, weather and climatic factors, as well as winter road maintenance measures. On curves of a small radius, braking or acceleration sections, as well as sections with a normal mode of movement of cars, the horizontal loads from the studded tire are different. This is due to the occurrence of various types of friction, as well as the dependence of the coefficient of adhesion of the coated tire on the speed of movement, which is variable in the braking and acceleration sections. As a result, in certain areas, the contribution of wear to the depth of the complex track is greater than in areas with a different driving mode. In the article, a study was conducted to determine the susceptibility of road sections with different traffic modes to the formation of wear ruts. A method has been developed for calculating various components of the complex trackage caused by compaction and wear of the asphalt concrete coating, as well as deformations of the underlying layers of the pavement and the roadbed.Result. Based on the data of experiments carried out on the roads of Omsk, a classification of sections according to the degree of danger to the formation of a wear track is proposed, dividing sections of urban roads into heavily worn, worn and weakly worn. Based on the analysis of data from road diagnostics performed over the past five years, the approximate service life of the coatings until the formation of a 30 mm deep track has been determined.Discussion and conclusion. The authors’ ideas about the influence of friction and the speed of movement on the process of track formation caused by wear are presented. The correspondence of the experimental data obtained by the authors of the article with the data of colleagues who performed similar studies in Russia and abroad is shown. Clarifications introduced by the authors into the generally accepted ideas about asphalt wear are explained.